Climate change and sustainability education in India and the place for arts-based practice: reflections from East Kolkata Wetlands (UCL Press, 2022)
In 2019 India was ranked seventh most affected nation by climate change, yet 65 per cent of the Indian population had not heard of climate change. India's revised National Education Policy mentions climate change and environmental issues as part of its work towards reaching the United Nation's Sustainable Development Goals. However, to date, climate education in India has tended to remain the responsibility of the secondary science teacher in many schools where resources are limited. Following calls for a more holistic and multidisciplinary approach - where students can link environmental issues with their lives - we reflect on three arts-based climate education exemplars with students from the East Kolkata Wetlands (EKW) (n = 150, 10-17-year-olds). We consider how these frame climate change and sustainable education as a collective learning experience, rather than as scientific concepts alone. We respond to Szczepankiewicz et al.'s model for climate education and propose that teacher training in the EKW context can be conceptualised through a three-stage, interconnected approach to pedagogy: building concepts, learning through hands-on activities and building communities is central. We suggest that these three generalisable tenets of student teacher practice should be explored in other areas of ecological fragility, as well as in spaces of economic insecurity.